(untitled) (Palíndromo, 2019)
This paper aims to analyze the use of Arabic calligraphy by pioneering art-ists of modern painting in Sudan in the 1950s and 1960s and its relationship to the country’s modernization process. The central role assigned to calligraphy in the curriculum of the Khartoum School, one of the main artistic movements on the African continent in the post-colonial period, will be problematized. The criti-cal debate led by Sudanese artists Has-san Musa and Abdallah Bashir (Bola) in the early 1970s, who saw the abstraction of Arabic calligraphy as a mechanism of essentialization of Sudanese art and cul-ture, will also be examined.